Мовні засоби відтворення світлотного контрасту в художньому моделюванні імпресіоністичної реальності (на прикладі українського письма) - Мішеніна, Тетяна; Mishenina, Tetyana (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розкрито мовні засоби вираження світлотного контрасту імпресіоністичного письма Михайла Коцюбинського відповідно до закономірностей художнього ритму, симетрії й рівноваги. Доведено взаємозв’язок характеру композиційних засобів передавання колірного навантаження твору із його конструктивною ідеєю. The article deals with the linguistic means of expression of black and white contrast of impressionist Michalo Kotsyubynsky letters in accordance with the laws of the art of rhythm, symmetry and balance. Proven relationship nature composite load transmission means color works with his constructive idea. Terms used in painting color, flavor served as the basis for the linguistic analysis of the text of the terms and color coloring vocabulary. From the theory of the fine arts are transferred not only the names but also the notion that they are invested. In particular, the term color realizes the value of a holistic, total interference colors on one another to influence the emotional and sensual sphere of man’s knowledge of the world.
Language Means of Displaying Black and White Contrast in Artistic Modeling Impressionistic Reality (for Example Ukrainian Writers)
Keywords: кольоратив; імпресіонізм; ідіостиль; світлотний контраст; художня композиція; синтетичний художній образ; color; impressionism; idiostyle; black and white contrast; artistic composition; a synthetic artistic image